Modernização do controle de nível de óleo nos mancais de escora da casa de força 2, na UHE-Tucuruí - SILVA, Sandra Meireles (2019)
The objective of this work is to show an improvement in the supervision of the oil level measurement system in the anchor bearing of the powerhouse two generating units of the Tucuruí Hydroelectric Plant. The anchor bearing is the system responsible for the vertical support of the turbine / generator set, composed of several segmented skates, immersed in an oil reservoir responsible for lubricating and cooling the same. This oil and lubricant thus requires a temperature and a volume that meets the turning conditions of the unit. The system that made these measurements consisted of an auxiliary tank with electromagnetic buoys, which triggered the reed switch’s according to their position, but it was presenting many problems, such as: low precision, no indication of volume, cracks due to weight Of the auxiliary tank, difficulties in maintenance. From these problems has thought itself in a more effective and easy maintenance. Then came an electronic level measurement system whose accuracy and functions were maximized, eliminating the critical problems of the system and reducing the difficulties of maintenance, improving in addition the security in the execution of the maintenance activities, using a Universal Digital Indicator (DMY-2030-Presys) connected to a pressure transducer (AISI316L).